Problem-Based Learning Models on Problem-Solving Ability and Science Learning Outcomes of Human and Environmental Concepts in Elementary Schools - Bumi Saputra, Wahyu Hafiz; Khaeruddin, Khaeruddin; Nurlina, Nurlina (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This study examines the effect of the Problem-Based Learning (PBL) model on problem-solving skills and science learning outcomes in fifth-grade students in Gugus III Baranti District, Sidrap. The approach used in this research is quantitative with the type of Quasy experimental design. The design used is the non-equivalent control group. The data collection techniques used in this study are as follows: First, pre-test and post-test, and second, observation. The observation sheet is used to obtain data regarding student activities during learning and classroom conditions during the learning process. Third, documentation is intended to get direct data from the research site. Based on the research results and data analysis, the following conclusions were obtained: First, Positive Effect on Problem-Solving Ability: The PBL model positively affects problem-solving skills on the material of the concept of humans and the environment. The significance value obtained is 0.000, more diminutive than 0.05, indicating that the PBL model effectively improves students' problem-solving ability. Second, Positive Effects on Science Learning Outcomes: The PBL Model also positively impacts science learning outcomes on the same material. The significance value obtained was also 0.000, confirming the effectiveness of the PBL model in improving students' understanding of the concept of humans and the environment. Applying the PBL Model effectively enhanced students' problem-solving skills and science learning outcomes. The significance value that is consistently smaller than 0.05 shows the consistency of the research results.